2013
DOI: 10.1590/s1984-82502013000400030
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and anti-inflammatory activities of several 4-substituted-6-(3'-nitrophenyl)pyridazin-(2H)-3-one derivatives

Abstract: Several 6-aryl-4-substituted benzylidene/furfurylidene pyridazin(2H)-3-one derivatives (4a-f) were synthesized and evaluated as analgesic and anti-inflammatory agents in mice and rats, respectively. All compounds were tested by using Eddy's hot plate and the carrageenan-induced hind paw oedema method for the evaluation of analgesic and anti-inflammatory activities, respectively. Results showed that compounds 4f, 4b, 4d, and 4e exhibited higher analgesic and anti-inflammatory activities than other remaining com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In recent years substituted pyridazinones have been a subject of demanding research due to their wide range of pharmacological actions 22,24 . Differently substituted pyridazinone derivatives were exhibited diverse potential pharmacological activities like an antidepressant, antihypertensive, anti-thrombotic, anticonvulsant, cardiotonic, analgesic, antiinflammatory, diuretics, antibacterial, anti-fungal, antiviral, anticancer, hypotensive, antiulcer and another biological activities 25,29 . (2H)-one (0.001 mol) in methanol (30 mL) was added formaldehyde (37-41%) (2.5 mL) and the contents were refluxed for 6 h. After completion of the reaction methanol was distilled off and the residue was poured into crushed ice to separate out the compound.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years substituted pyridazinones have been a subject of demanding research due to their wide range of pharmacological actions 22,24 . Differently substituted pyridazinone derivatives were exhibited diverse potential pharmacological activities like an antidepressant, antihypertensive, anti-thrombotic, anticonvulsant, cardiotonic, analgesic, antiinflammatory, diuretics, antibacterial, anti-fungal, antiviral, anticancer, hypotensive, antiulcer and another biological activities 25,29 . (2H)-one (0.001 mol) in methanol (30 mL) was added formaldehyde (37-41%) (2.5 mL) and the contents were refluxed for 6 h. After completion of the reaction methanol was distilled off and the residue was poured into crushed ice to separate out the compound.…”
Section: Methodsmentioning
confidence: 99%
“…Results showed that furfurylidene derivative 35 was more potent for in vivo anti-inflammatory activity than other substituted benzylidene derivatives (Figure 24). [62] Moreover, compound 35 showed 40% inhibition of edema compared to indomethacin (44.53% inhibition of edema).…”
Section: Anti-inflammatory Activity Of 26-disubstituted Pyridazinonesmentioning
confidence: 97%
“…The compounds (1-8) showed mild to moderate anticonvulsant activity ranging from 0.0% to 50% in Table 3. Indomethacin was taken as standard drug [31][32][33] . Table 4.…”
Section: Anti-convulsant Activitymentioning
confidence: 99%